“I am resting but rest less well with you.” The moderating effect of anxious attachment style on alpha power during EEG resting state in a social context - Verbeke, Willem J. M. I.; Pozharliev, Rumen; Van Strien, Jan W.; Belschak, Frank; Bagozzi, Richard P. (Frontiers in Human Neuroscience, 2014)
We took EEG recordings to measure task-free resting-state cortical brain activity in 35 participants under two conditions, alone (A) or together (T). We also investigated whether psychological attachment styles shape human cortical activity differently in these two settings. The results indicate that social context matters and that participants’ cortical activity is moderated by the anxious, but not avoidant attachment style. We found enhanced alpha, beta and theta band activity in the T rather than the A resting-state condition, which was more pronounced in posterior brain regions. We further found a positive correlation between anxious attachment style and enhanced alpha power in the T versus A condition over frontal and parietal scalp regions. There was no significant correlation between the absolute powers registered in the other two frequency bands and the participants’ anxious attachment style.